2020
DOI: 10.13189/ujer.2020.080217
|View full text |Cite
|
Sign up to set email alerts
|

Improving Prospective Primary School Teachers' Mental Models through Implementation of CDOI Supported by Multimode Visualization

Abstract: This study aims to improve the mental model of prospective primary school teacher related to the concept of boiling through the implementation of the conceptual development-oriented instruction (CDOI) model assisted by multimode visualization. This research was conducted using the pre-experimental method with the design of one group pretest-posttest. The subjects of the study were 36 the prospective primary school teachers, consisting of 20 female and 16 males. The research location is one of the universities … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…When all the findings were considered, it was revealed that the PPSTs could not think in a triple structure (macroscopic, sub-microscopic, and symbolic) and could not combine them in related content of the crystallization experiment. As emphasized in the literature (Banawi et al, 2019;Derman & Ebenezer, 2020;Hermita et al, 2020) and found in this study, the understanding of prospective primary school teachers require to include macroscopic, sub-microscopic, and symbolic levels.…”
mentioning
confidence: 81%
See 2 more Smart Citations
“…When all the findings were considered, it was revealed that the PPSTs could not think in a triple structure (macroscopic, sub-microscopic, and symbolic) and could not combine them in related content of the crystallization experiment. As emphasized in the literature (Banawi et al, 2019;Derman & Ebenezer, 2020;Hermita et al, 2020) and found in this study, the understanding of prospective primary school teachers require to include macroscopic, sub-microscopic, and symbolic levels.…”
mentioning
confidence: 81%
“…Quality science education can offer students various mental processes to acquire higher cognitive skills and representations. At this point, it is highly crucial to use dynamic analogies (Hermita et al, 2020), activities such as experiments, animations, educational videos (Akkuzu Güven & Uyulgan, 2021), and online activities (Polifka, 2021) to reveal representations and to provide meaningful learning. According to recent studies, these activities help students observe, investigate, and understand the physical world through direct experiences with the phenomena or manipulating objects and materials (Akkuzu Güven & Uyulgan, 2021;Banawi, Sopandi, Kadarohman, & Solehuddin, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…With regard to the change of teacher mindsets, Hermita et al (2020) study the concept of boiling of some prospective primary school teachers, through the implementation of the conceptual development-oriented instruction model. Corrochano and Gonçalves (2020) analyze the change of some Spanish pre-service teachers' mental models of geologic time, and find that the mental model that is repeated the most before and after instruction is still quite far from the scientific model.…”
Section: Change (Or No Change) Of Teacher Mindsetmentioning
confidence: 99%
“…Learning is essentially a process of interaction that takes place in an educational situation to achieve learning goals. Learning carried out in a home, or school environment will impact students' attitudes (character) and mental [1]- [6] School as a learning organization has an essential role in guiding students to reach a development level by optimizing developmental tasks. In the formation of learning organizations, schools must be able to encourage five core things, namely: 1) Systems Thinking, 2) Personal Skills (Personal Mastery), 3) Mental Model, 4) Shared Vision (Building Shared Vision), and 5) Team Learning (Team Learning) [3].…”
Section: Introductionmentioning
confidence: 99%